Acanthocephala Larvae parasitizing Ameiva ameiva ameiva (Linnaeus, 1758) (Squamata: Teiidae) - Macedo,Lilian Cristina (2016)
Abstract Knowledge concerning the taxonomy and biology of species of Acanthocephala, helminth parasites of the helminth species of the phylum Acanthocephala, parasites of lizards in Brazilian Amazonia, is still insufficient, but reports of Acanthocephala in reptiles are becoming increasingly common in the literature. Cystacanth-stage Acanthocephalan larvae have been found in the visceral peritoneum during necropsy of Ameiva ameiva ameivalizards from the “Osvaldo Rodrigues da Cunha” Herpetology Collection of the Emílio Goeldi Museum, Belém, Pará, Brazil. The aim of this study was to present the morphological study of the Acanthocephala larvae found in A. ameiva ameiva lizard.